On the nilpotency of some modules over group rings - Kurdachenko, L.; Pypka, O.; Subbotin, I. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.553 We study RG-modules that do not contain nonzero G-perfect factors. In particular, it is shown that if a group G is finite and R is a Dedekind domain with some additional restrictions, then these RG-modules are G-nilpotent.